2020
DOI: 10.5747/ca.2020.v16.n3.a369
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo de amendoim em função da adubação e do espaçamento entre plantas em sistema de sequeiro e irrigação complementar

Abstract: In the rigion Nordeste, the peanutis cultivated almost exclusively by family agriculture producers with low technological levels, in addition to the low use of inputs, essential to ensure better productivity. Objective to evaluate the performance and productivity of peanut subjected to doses of fertilization and spacing between plants, in the rainfed system and irrigation system. The experiment was conducted at the Federal University of cariri. Two experiments were conducted in randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…This result is possibly related to K participating in protein synthesis and carbohydrate transport, favouring the quality of the fruit and vegetables. Pinto et al (2020) found a positive effect from potassium fertiliser in the peanut. The authors describe how the recommended dose afforded greater pod weight.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…This result is possibly related to K participating in protein synthesis and carbohydrate transport, favouring the quality of the fruit and vegetables. Pinto et al (2020) found a positive effect from potassium fertiliser in the peanut. The authors describe how the recommended dose afforded greater pod weight.…”
Section: Resultsmentioning
confidence: 95%
“…Efeito positivo da adubação potássica, na cultura do amendoim, foi verificado por Pinto et al (2020). Os autores descrevem que a dose recomendada proporcionou maior massa de vagem.…”
Section: Resultsunclassified
See 3 more Smart Citations